Distributed systems and trusted execution environments: Trade-offs and challenges - Pires, Rafael Pereira; Felber, Pascal; Pasin, Marcelo (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2020)
This extended abstract summarises my PhD thesis, which explores design strategies for distributed systems that leverage trusted execution environments (TEEs). We aim at achieving better security and privacy guarantees while maintaining or improving performance in comparison to existing equivalent approaches. To that end, we propose a few original systems that take advantage of TEEs. On top of prototypes built with Intel software guard extensions (SGX) and deployed on real hardware, we evaluate their limitations and discuss the outcomes of such an emergent technology.